Drug Reprofiling: A Prospective Approach to Battle Chronic Ailments - Aggarwal, Natasha Naval; Sindhoor, S.M.; Naveen, N. Raghavendra; Gowthami, Buduru; Biju, Prajitha (Journal of Health and Allied Sciences NU, 2023)
The concept of drug “reprofiling” has garnered attention in the recent past post the outbreak of coronavirus disease 2019 when traditional drug discovery seemed to fail. Even though repurposing is called pharma-friendly in terms of monetary relief, clinical trials play an integral role in repurposed nontarget /combination moieties. Nevertheless, when a drug exhibits no returns to the market, an exhaustive study on mechanism of action (MOA) can help for reprofiling of drugs for new indications. However, several papers have claimed that scarcity of resources and data access, and staffing issues, tends to pull down reprofiling of drugs. In contrast to this notion, a total of 155 patented articles to date give a strong base for drug repurposing. In the present review, a scientific prospection of reprofiled antifungal and antiviral agents for the past decade was made using the PubMed database wherein a total of 410 and 768 publications have resulted respectively. The authors have attempted to focus their attention to repurposing antifungal drugs for chronic ailments and infectious diseases by understanding their MOA.For example, antifungal azoles, which work by blocking ergosterol synthesis, can be repurposed as they inhibit histone deacetylase as well significantly decrease the production of cytokines and modulate the inflammatory pathways used by cancer cells.Hence, we believe that the mentioned Food and Drug Administration-approved drug candidates can be utilized to treat nontarget diseases, notably rare/neglected diseases as well as chronic illnesses and the more recent viral infections that are spreading globally.
Keywords: antibiotic; FDA-approved; tumors